Promoter Methylation of QKI as a Potential Specific Biomarker for Early Detection of Colorectal Cancer - Lei Zhang; Dapeng Li; Lijing Gao; Jinming Fu; Simin Sun; Hao Huang; Ding Zhang; Chenyang Jia; Ting Zheng; Binbin Cui; Yanlong Liu; Yashuang Zhao (Frontiers in Genetics, 2022)
Early and specific detection of cancer provides an opportunity for appropriate treatment. Although studies have suggested that QKI is a tumor suppressor gene, no studies have evaluated the diagnostic utility of QKI methylation in colorectal cancer (CRC). Here, we evaluated the methylation status of QKI by integrating the methylation data of tissues and cell lines of multiple cancer types. The diagnostic performance of QKI was analyzed in the discovery dataset from the TCGA CRC 450K array (n = 440) and tested in the test sets (n = 845) from the GEO. The methylation level of QKI was further validated in our independent dataset (n = 388) using targeted bisulfite sequencing. All detected CpG sites in the QKI promoter showed CRC-specific hypermethylation in 31 types of tumor tissues. In the discovery dataset, six consecutive CpG sites achieved high diagnostic performances, with AUCs ranging from 0.821 to 0.930. In the test set, a region (chr6: 163,834,452–163,834,924) including four consecutive CpG sites had robust diagnostic ability in distinguishing CRC and adenoma from normal samples. In the validation dataset, similar robust results were observed in both early- and advanced-stage CRC patients. In addition, QKI exhibited hypermethylation in the cfDNA of patients with CRC (n = 14). Collectively, the QKI promoter is a CRC-specific methylation biomarker and holds great promise for improving the diagnosis using minimally invasive biopsy.